Perancangan Sistem Informasi Akuntansi Persediaan Obat Berbasis Desktop Di Poliklinik Pusdikmin Lemdiklat Polri - Mia Nurlina (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The purpose of designing a drug inventory accounting information system is to speed up the delivery of drug availability information and make it easier to search for effective and efficient drug data. The author uses data collection techniques by means of literature studies, documentation, interviews and observations. Even though in recording and making inventory reports, it is still a semi-computer with Microsoft Excel , but there are several problems that may occur, including the officers having difficulty in recording the number of incoming and outgoing drugs, the truth of the calculation is not guaranteed and there is a delay in the delivery of information. The author designed an inventory accounting information system using structured analysis accompanied by MySQL as the database, Entity Relationship Diagrams (ERD) programming language VB.Net, Data Flow Diagrams (DFD), and FlowMap. The system development method used is the Waterfall model. By testing the system using black box. The author hopes that this application can help the performance of officers in processing drug inventory data.